Parietal lobe variation in cercopithecid endocasts. Issue 7 (26th June 2019) - Pereira‐Pedro, Ana Sofia; Beaudet, Amélie; Bruner, Emiliano
Abstract: In extant primates, the posterior parietal cortex is involved in visuospatial integration, attention, and eye‐hand coordination, which are crucial functions for foraging and feeding behaviors. Paleoneurology studies brain evolution through the analysis of endocasts, that is molds of the inner surface of the braincase. These may preserve imprints of cortical structures, such as sulci, which might be of interest for locating the boundaries of major cortical regions. Old World monkeys (Cercopithecidae) represent an interesting zoological group for evolutionary studies, because of their diverse ecologies and locomotor behaviors. In this study, we quantify parietal lobe variation within the cercopithecid family, in a sample of 30 endocasts including 11 genera and 17 species, by combining landmark‐based and landmark‐free geometric morphometric analyses. More specifically, we quantitatively assess variation of the parietal proportions based on landmarks placed on reliable anatomical references and of parietal lobe surface morphology through deformation‐based methods. The main feature associated with the cercopithecid endocranial variation regards the inverse proportions of parietal and occipital lobes, with colobines, Theropithecus, and Papio displaying relatively larger parietal lobes and smaller occipital lobes compared with cercopithecins. The parietal surface is anteroposteriorly longer and mediolaterally flatter in colobines, while longitudinally shorter but laterally bulging in baboons. Large parietal lobes in colobines and baboons are likely to be independent evolutionary traits, and not necessarily associated with analogous functions or morphogenetic mechanisms. Abstract : Endocranial casts can be useful for studying brain evolution in fossil specimens. Geometric morphometrics analysis of cercopithecid whole endocast and parietal‐only shape variation evidences larger parietal lobes in colobines and in baboons compared to other cercopithecines. HIGHLIGHTS: Sulcal imprints on the surface of cercopithecid endocranial casts have shown differences between the two subfamilies, cercopithecinae and colobinae. Landmark‐based analysis allowed a quantification of these differences, confirming colobines have proportionately larger parietal lobes. Theropithecus and Papio display colobine‐like proportions. Colobuses and baboons evolved a larger parietal cortex through distinct mechanisms.